DEVELOPMENT OF FRANCHISE IN SMALL HOTEL BUSINESS - M. Zhukova (Вестник университета)
The study is aimed at identifying trends in the development of small accommodation facilities in the world, to which it is appropriate to include hostels. Examples of the development of hostels in Europe and the USA are considered, such tendencies of their development as boutique hostels creation, formation of various kinds of associations / associations and use of the network form of organization of activity are revealed. In addition, the trends in the development of hostel networks in Russia, the conditions for buying a franchise, the problems of functioning and ways to solve them are analyzed.